Rancangan Teknis Pushback Penambangan Batu Bara di Pit Block 01 PT. Borneo Alam Semesta Site PT. Binuang Mitra Bersama Kecamatan Lokpaikat Kabupaten Tapin Provinsi Kalimantan Selatan - Wahdian Noor, Ahmad; Supandi; Sidiq, Hidayatullah (Retii, 2023)
PT. Borneo Alam Semesta is a national private company engaged in coal mining contracting at PT. Binuang Mitra Bersama which is located in Budimulya Village, Lopaikat District, Tapin Regency, South Kalimantan Province. PT. Binuang Mitra Bersama as the owner has a production operation mining permit (IUP) covering an area of 537,48 Ha. PT. Binuang Mitra Bersama requires an annual production target of ± 850.000 tons with an average stripping ratio of ± 4:1 according to a predetermined target.Based on the annual mine progress plan that has been made and from the results of volume calculations in the pit, an estimated mining life of pit bmb block 01 is 3 years 4 months with an average number of loading and unloading equipment per year of ± 6 units. In the first year of miningthe volume of overburden uncovered was 3.547.795 Bcm and coal was 857.301 tons. In the second year of mining the volume of overburden uncovered was 3.531.342 Bcm and coal was 860.745 tons. In the third year of mining the volume of overburden uncovered was 3.427.688 Bcm and coal was 879.663 tonnes. and in mining in the last year the volume of overburden uncovered was 865.238 Bcm and coal was 324.643 tons.Keywords: Stripping Ratio, Production Scheduling, Mine Life